Using the diffusion of innovations theory to understand factors associated with COVID-19 vaccination among tobacco users. - Gail Carmen D'Souza; Jessica M Yingst; Nicolle M Krebs; Candace Bordner; Sophia I Allen; William A Calo; Andrea L Hobkirk; Jonathan Foulds (PLoS ONE)
The coronavirus disease (COVID-19) pandemic has spread in the US with more than 100 million human infections and a million deaths since March 2020. A population of concern are high-risk individuals such as adults who are tobacco users, since COVID-19 is a respiratory disease that affects the lungs. Although 79% of the US population ≥ 18 years of age have completed the primary COVID-19 vaccine series; it is imperative to understand the factors associated with receiving or declining the COVID-19 vaccine among high-risk populations to improve vaccination rates. Guided by the diffusion of innovations (DOI) theory, this study identified factors associated with COVID-19 vaccination and the impact on COVID-19 vaccine uptake in adults who use tobacco. We conducted a cross-sectional study using a sample of Pennsylvanian adult tobacco users by sending a unique survey link to 4,081 email addresses in April 2022. Participants were asked about tobacco use, COVID-19 vaccination status, and reasons for receiving/declining the COVID-19 vaccine. Participants (n = 157) were 75% female, 96% White, 74% current tobacco users, and had a mean age of 50.1 (SD = 10.8) years. Nearly 78% (n = 119) received at least one dose of the COVID-19 vaccine (primary series). We categorized all vaccinated tobacco users into adopter categories of the DOI theory; innovators (10%), early adopters (14%), early majority (33%), late majority (11%), and laggards (32%). The major reason that prompted participants to get the COVID-19 vaccine was to ensure they were well protected against COVID-19 infection (77%). Additionally, the only reason for receiving the vaccine that significantly predicted early vaccine uptake (being an innovator or early adopter) was "to loosen restrictions on mask mandates and social/physical distancing" (p = 0.0180). Among the 22% that did not receive a COVID-19 vaccine, the most common major reason they declined the vaccine was because they felt politics played a big role in the vaccine development process (94%). Our findings suggest that major f actors that influenced why adult tobacco users would receive or decline the COVID-19 vaccine included infection control mandates, protection from the COVID-19 infection, and politics. Investigating these factors can help public health professionals design or develop future vaccination programs for high-risk populations in order to scale up vaccination rates.